Experimental investigations on microstructure and mechanical properties of wall structure of SS309L using wire-arc additive manufacturing - Rakesh Chaudhari; Sakshum Khanna; Jay Vora; Vivek Patel (Journal of Advanced Joining Processes, 2024)
In present study, a wall structure of SS309L was constructed through Gas metal arc welding based Wire-arc additive manufacturing process. The wall structure of SS309L underwent investigation for microstructure and mechanical properties at three positions along the horizontal deposition direction. Mechanical assessments, including microhardness testing, impact testing, tensile testing, and fractography, were conducted at three positions of walls. Microstructure study has shown a fine granular structure in addition to colony of columnar dendrites in bottom section, a columnar dendrites in middle section, and a mix of dendritic structure with even coarser structures in top section. The mean microhardness values were observed to be 159 ± 4.21 HV, 162 ± 3.89 HV, and 168 ± 5.34 HV for the top, middle, and bottom sections, respectively. Results of impact testing for the wall structure indicated greater strength compared to wrought SS309L. The tensile strength of the built structure showed average values of yield strength, ultimate tensile strength, and elongation to be 409.33 ± 7.66 MPa, 556.66 ± 6.33 MPa, and 39.66 ± 2.33 %, respectively. In comparison, wrought 309 L steel typically exhibits tensile strengths in the range of 360–480 MPa for yield strength, 530–650 MPa for ultimate tensile strength, and 35–45 % elongation. Thus, the obtained tensile strength results for the wall structure fall within the range of tensile strength observed in wrought 309 L steel. Fractography of the tensile and impact specimens, as obtained through Scanning Electron Microscopy, revealed the superior ductility of the fabricated component. This study contributes valuable insights into the manufacturing of wall structure and their analysis regarding mechanical characteristics.